Influence of maximum heart rate predicts method on appropriate exercise intensity via Algerian soccer training programs - Zerf Mohammed (Türk Spor ve Egzersiz Dergisi)
Our aim in this current study aspect the influence of predicts method in estimating exercise intensity associated with maximum heart rate assessment. In lack of beeps system tools, training analysis software as new high-tech to track intensity. While our coaches’ base their loads exercise on the formula: 220 minus ages, in within their players estimate their maximum heart rate, adapts to their intensity exercise in performing this latter during the weekly exercises. In order to test these practices and judge their efficacy or inadequacy. Sixty-two male elite Algerian players, first League division one at Oran Algerian Championship teams, year (2015-2016). Participate in the present study, their homogeneous were calculated on the basis of 6 min intentional athletic exercise, as protocol used to calculate the VO2max estimate from Cooper test 6 min and RHR uses the polar watch system to compute Heart Rate. Although Max Heart zones exercise was built on formula Uth N as a procedure to calculate the intensity. Backed by differences gained, according to protocol proposed in which the energy dominant is relative to maximum heart rate corresponding to exercise intensity. We reject the measures taken by our coaches, which are not operative to esteem the maximum heart rate connected to the request VO2max and HRrest associated with exercise intensity planned. While as a recommendation, we required our coaches to use the beeps automated training system tools as polar watch beep system to establish the exercise intensity consistent with exercise maximum heart rate and energy requirements. Using our formula Max Heart zones exercise = (VO2max/15) * Heart Rate, derived from formula Uth N.